The Impact of Emotional Intelligence on Soft Skill Development in Elementary School Student Learning - Liestyowati, Liestyowati (Mimbar Sekolah Dasar, 2025)
The development of students’ social-emotional skills remains limited and tends to focus primarily on cognitive aspects and academic subject mastery. This research is important because students require strong soft skills to succeed in various life contexts. The study aimed to examine the effectiveness of emotional intelligence-based learning methods in enhancing students’ soft skills. A mixed-methods approach was employed, involving 730 purposively selected elementary school students from the Bandung area. Data were collected through Likert-scale questionnaires, in-depth interviews, observations, and documentation of the learning process at elementary schools in Buahbatu, Bandung. Quantitative data were analyzed using descriptive and inferential statistics with SPSS Version 29.0, while qualitative data were analyzed through data collection, reduction, coding, and interpretation of coding results. The findings revealed a significant improvement in students’ communication skills, empathy, emotional regulation, and collaboration after participating in the emotional intelligence-based learning program. Furthermore, the enhancement of students’ soft skills was closely linked to the effective management of their emotional intelligence. In conclusion, the development of learning programs that integrate personal skills can serve as an educational model supporting the curriculum. The practical implication is that fostering social-emotional competence equips students with essential abilities to meet future challenges.